Metal concentration and its ecological risk assessment in the beach sediments of Coromandel Coast, Southern India. (November 2020) - Sanjai Gandhi, K.; Pradhap, D.; Saravanan, P.; Krishnakumar, S.; Kasilingam, K.; Sukanta Patel, H.; Prakash, P.; Muthukumaran, S.; Magesh, N.S.
Abstract: The present study investigates the concentration of acid leachable trace metals (ALTMs) and their ecological risk in the beach sediments of Coromandel Coast, Southern India. In total, thirty-six beach sediments (eighteen samples from low tide and eighteen samples from high tide) were collected from the study area. The results of the study of the ALTMs suggest that the sediments are enriched by natural processes with significant anthropogenic influences. The distribution of ALTMs in beach sediments is in the following descending order: Fe > Cr > Mn > Pb > Ni > Cu > Co > Zn. The statistical results indicate that the metal concentrations were chiefly originated from natural processes such as leaching, weathering, and fluvial action. In addition, the textural characteristics, organic matter, and calcium carbonate percentage play an important role in the distribution of metals in the beach sediments. Highlights: The concentration of ALTMs and ecological risk of the Coromandel coast was assessed. Concentration shows the following order: Fe > Cr > Mn > Pb > Ni > Cu > Co > Zn. The source of metals is from natural weathering and anthropogenic activities.